The Mediating Role of Administrative Assistance on the Influence of Digital Competency and ICT Practice on Online Teaching Performance - Dulay, Michelle (12th International Scholars Conference 2025, 2026)
The COVID-19 pandemic catalyzed an urgent shift to online learning, exposing challenges in teacher readiness and institutional support systems. This study investigates the mediating role of administrative assistance in the relationship between digital competency, ICT Practice and online teaching performance among private secondary school teachers in the Philippines. Using a quantitative research design and Structural Equation Modeling (SEM), data were collected from 318 teachers across Luzon, Visayas, and Mindanao through a structured online questionnaire. Results revealed that while teachers demonstrated high digital proficiency and effective ICT practices, their performance was significantly enhanced when supported by strong administrative assistance. This assistance encompassed managerial, logistical, and emotional support that mitigated non-teaching burdens and facilitated effective technology integration. Mediation analysis confirmed that administrative assistance partially mediated the influence of both digital competency and ICT practice on online teaching performance. Furthermore, demographic factors such as age, sex, and years of teaching experience moderated the strength of these relationships, indicating the importance of context-specific support strategies. The findings emphasize that digital skills alone are insufficient; institutional support, particularly administrative assistance, is a critical enabling factor for effective online instruction. The study contributes to the understanding of how school leadership and systemic support play pivotal roles in sustaining digital education, offering implications for policy, training, and educational reform in response to future disruptions.